An investigation into the effects of border carbon adjustments on the Canadian economy - Henry Hosseini Chen; Craig Johnston; Sergey V. Paltsev; Marie-Christine Tremblay (Bank of Canada, 2024)
This paper examines how border carbon adjustments (BCAs) may address the unintended consequences of uncoordinated global climate action, focusing on the economic implications for Canada. We investigate these implications under different BCA design features and by considering a coalition of countries and regions that adopt BCAs. We find that BCAs, in the form of import tariffs, reduce Canada's carbon leakage to the rest of the world and improve its domestic and foreign competitiveness when Canada is part of a coalition of countries and regions that implement BCAs that includes the United States. We show that these results may change if Canada imposes BCAs on a different set of sectors than the rest of the coalition or includes export rebates and free emissions allowances to firms. When the United States is not part of the coalition, we show that Canada's carbon leakage increases, domestic competitiveness dampens and foreign competitiveness improves. Compared with a case where no countries have BCAs, welfare improves in Canada if revenues from BCAs, in the form of import tariffs, are transferred to households. This finding holds regardless of the United States' participation in the coalition.
Keywords: C68; F1; H2; Q5; Q37; 330; Climate change; International topics; Trade integration